KUALITAS PRODUK MAKANAN DI KITCHEN DEPARTMENT HOTEL GRAND JATRA PEKANBARU - Yesi Rahmadani; Mariaty Ibrahim (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
Food and Beverage Product (Kitchen Department) is one of the departments in the hotel that has a very large role. This section is in charge of providing food for hotel guests. The quality of the food produced must be improved. Therefore, every hotel must have a strategy to improve the quality of the food that will be produced. This study aims to determine the quality of food products by the kitchen epartment at the Grand Jatra Hotel Pekanbaru. This study uses a qualitative method with a descriptive approach. The data collection techniques used were observation, documentation, and interviews with the Executive Chef and Chef de Partie Grand Jatra Hotel Pekanbaru. After conducting interviews with informants, the authors conclude that the quality of food products produced by the kitchen department can be said to be good. But the kitchen department must further improve the quality of its food products so that it can satisfy guests who enjoy it. Keywords : Quality, Food, Kitchen department